Karsinoma rektum di kalangan pesakit Hospital Kuala Lumpur - Azidah A.H.,; Azmi S.,; Hanisah A.,; Hasmah H.,; Low, H.C.; Norshamsiah M.D.,; Ramesh S.,; Tan, C.E. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1995)
A case control study was caried out on 30 patients with rectal carcinoma chosen from the wards of Hospital Kuala Lumpur from January 1991 to June 1994. The purpose of this study was to determine whether diabetes mellitus, hypertension, smoking and the consumption of alcohol were risk factors for rectal carcinoma. The relevant data was obtain from the patient Medical Records. Another 30 patients were chosen as the control group who are free from any cancer. They were chosen at random from the other wards of Hospital Kuala Lumpur. This study found that only smoking is a risk factor for rectal carcinoma.